Cultural surveys and Finnish cultural policy - Toledo Ramirez, Sandra (2017)
The following thesis revolves around the research question what is the role of cultural surveys in Finnish cultural policy? In order to try to answer this question, elements were taken into consideration involving the relationship between these types of surveys and trends followed in Finnish cultural policy. Among the elements analysed were: the model of cultural policy in Finland and its shifts, the main cultural surveys carry out in Finland, the cultural surveys at a local level using as an example the case of Helsinki, and the adoption of indicators as measurements for effectiveness in public policy.